Compostos com potencial alelopático em Aristolochia esperanzae O. Kuntze - Jatoba, Luciana de Jesus (Universidade Federal de São Carlos, 2012)
ABSTRACT Allelopathy is defined as any process involving secondary metabolites that influence the growth and development of natural and cultivated systems. Plants of the Aristolochia genus are known for their use in traditional medicine, but few studies have been conducted on the ecological importance of their secondary compounds and their possible application in agriculture. This study aimed at the isolation, characterization and evaluation of the allelopathic activity of A. esperanzae secondary metabolites. Extraction, bioassay-guided isolation, spectroscopic and spectrometric analysis of the isolated compounds was carried out. The phytotoxic activity of the active extracts from A. esperanzae different organs on the development of species of cultivated crops and weeds, and of the active semipurified sample in the initial growth of Triticum aestivum L. (wheat) was evaluated. The EtOAc extracts of A. esperanzae mature leaves and roots showed phytotoxic activity similar to the herbicide used as control over the weed species. Biossayguided isolation of compounds with allelopathic activity from mature leaves of A. esperanzae has led to the isolation of three isomeric compounds with mass fragments with m/z 321 Da and 161 Da, and ultraviolet absorption at 234 nm and between 286 nm and 287 nm. Analysis by 1D- and 2D-NMR of one of these compounds allowed to stabilish its partial structure. The semi-purified ISO sample, obtained from A. esperanzae mature leaves and composed mainly by the isomeric mixture isolated, showed allelopathic activity on the early development of wheat, with inhibition of root development and formation of necrotic abnormalities over the shoots of these seedlings, with hormetic behavior. The activity of the compounds present in the ISO fraction showed to be different from that presented by the commercial herbicide, and may lead to the development of bioherbicides..
Keywords: Ecologia; Aleloquímicos; Estudo fitoquímico; Isolamento biodirigido; Fitotoxicidade; Bioherbicidas; Cipó-mil-homens; Keywords: Allelochemicals, phytochemistry study, biossay-guided isolation, cipó-mil-homens, phytotoxicity, bioherbicides; CIENCIAS BIOLOGICAS::ECOLOGIA